2013
DOI: 10.3109/09273948.2013.791700
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal Gland Uptake of67Ga-gallium Citrate Correlates with Biopsy Results in Patients with Suspected Sarcoidosis

Abstract: Lacrimal biopsy positivity rate significantly correlated with gallium uptake on scintigraphy. Both SVS and LUR methods appear to correlate with histologic results and may potentially aid in patient selection for biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
0
3
0
1
Order By: Relevance
“…However, preclinical and clinical studies demonstrated the applicability of [ 68 Ga]Ga‐citrate and better imaging characteristics in detection of acute osteomyelitis and intra‐abdominal infection . Based only on publications from 2013 to June 2014, the translation of 67 Ga/SPECT experience to 68 Ga/PET could potentially be useful for diagnosis of sarcoidosis, reticulohistiocitosis, osteomyelitis and discitis, diabetic foot osteomyelitis, cancer, infected aneurysm, cytophagic histiocytic panniculitis and fungal discitis . In addition, it should also be mentioned that [ 67 Ga]Ga‐citrate has been used for clinical diagnosis of lung cancer, malignant melanoma, leukaemia and some other neoplasms.…”
Section: Miscellaneousmentioning
confidence: 99%
“…However, preclinical and clinical studies demonstrated the applicability of [ 68 Ga]Ga‐citrate and better imaging characteristics in detection of acute osteomyelitis and intra‐abdominal infection . Based only on publications from 2013 to June 2014, the translation of 67 Ga/SPECT experience to 68 Ga/PET could potentially be useful for diagnosis of sarcoidosis, reticulohistiocitosis, osteomyelitis and discitis, diabetic foot osteomyelitis, cancer, infected aneurysm, cytophagic histiocytic panniculitis and fungal discitis . In addition, it should also be mentioned that [ 67 Ga]Ga‐citrate has been used for clinical diagnosis of lung cancer, malignant melanoma, leukaemia and some other neoplasms.…”
Section: Miscellaneousmentioning
confidence: 99%
“…The panda pattern is associated with a symmetrical uptake in parotid and lacrimal glands, as well as in submandibular and sublingual salivary glands. The constellation of the lambda and panda pattern uptake is recognised as very characteristic for sarcoidosis [17,44]. Gallium-67 scintigraphy is more sensitive than an X-ray scan and can be applied for the evaluation of the staging of the disease activity, for the assessment of treatment results, and for the prediction of relapses.…”
Section: Gallium-67 Scintigraphymentioning
confidence: 99%
“…Вовлечение слезной железы в патологический процесс часто происходит бессимптомно, хотя в ряде случаев может приводить к развитию кератоконъюнктивита и диплопии. Об этом свидетельствует факт накопления галлия-67 ( 67 Ga) в слезных железах у 88% больных при отсутствии клинических и функциональных изменений слезной железы [9].…”
Section: Introductionunclassified